(untitled) (Research, Society and Development, 2022)
Infection by the protozoan Lophomonas spp is a rare condition, with just over 250 cases described worldwide, none of them in Brazil. This infection is mostly associated with states of immunosuppression and poor hygiene conditions in underdeveloped countries. The objective of this article is to report the first Brazilian case of bronchopulmonary lophomoniasis in a male individual concomitantly with Severe Acute Respiratory Syndrome (SRAG) caused by the new coronavirus (SARS-CoV-2) and pulmonary tuberculosis. During the investigation of the respiratory condition, the patient presented a solitary cavitated nodule in the imaging exam, being submitted to a bronchoalveolar lavage that showed the presence of the protozoan of the genus Lophomonas spp. Drug treatment with Metronidazole was started for 14 days, with clinical improvement, with interruption of fever and subsequent extubation. Thus, it is important to consider the variety of etiological possibilities in infectious conditions of the respiratory tract that do not respond to conventional therapy used for bacterial and fungal pneumonia.